Психологічна допомога працівникам правоохоронних органів, які виконували службові обов’язки в нетипових умовах - Кудар, К. В.; Kudar, K. V.; ORCID: http://orcid.org/0000-0002-1925-6431 (Право і безпека. – 2017. – № 2 (65). – С. 12–17, 2017)
Описано сучасні підходи та методи психології, які застосовуються в роботі з людьми з посттравматичними стресовими розладами, розладами адаптації тощо. Проаналізовано можливості використання самодопомоги, дебрифінгу тощо в роботі з працівниками правоохоронних органів, які виконували службові обов’язки в нетипових умовах. Показано дієвість різних методів психології залежно від етапу надання психологічної допомоги та складності симптоматики. Наполягається, що психологічна самоосвіта, взяття відповідальності на себе за свій стан, оволодіння навичками правильної поведінки та позитивне мислення є важливими в реабілітації правоохоронців, які виконували службові завдання в нетипових умовах.

Execution of official duties in the anti-terrorist operation (ATO) in the East of Ukraine requires from the officers a significant reorganization of their psyche, which can lead to an internal conflict between the instinct of self-preservation and the duty to protect and stand up to the end, however it is terrible and hurts. Inaccessibility of psychological assistance, dissatisfied needs for the recognition, support, etc., as well as psychological trauma and abrupt change in conditions from close to combat to ordinary, peaceful professional conditions can cause a number of disorders that complicate adequate adaptation to the surrounding environment. In order to facilitate the process of adaptation, psychologists tirelessly study not only the directions and psychological techniques that can help with this problem, but also the degree of their effectiveness and utility depending on the complexity of the state and symptoms. At this stage of the development of psychology, scholars believe that the main approaches to work with post-traumatic stress disorder (PTSD) and disorders of adaptation are behavioral, cognitive, client-centered, as well as psychodynamic approaches. During psychological work, the emphasis shifts from symptomatology to the image and meaning of psycho-trauma. Besides, according to scholars, the most adequate sequence of the provision of psychological care methods after the performance of military and combat tasks in non-typical conditions are: the methods directed to work with the body, the formation of self-help skills (body-oriented therapy, respiratory techniques, relaxation trainings, etc.); group work, debriefing, aimed at finding out the issues, remembering the traumatic events, discussing useful strategies to overcome the effects of extreme events, rather than treating personal traumatic feelings; individual counseling for the purpose of working out negative feelings and conditions and updating of resource states; group, individual or family psychotherapy. Psychological self-education, taking responsibility for yourself for your condition, mastering the skills of correct behavior and positive thinking can also be effective assistance.

Описаны современные подходы и методы психологии, которые применяются в работе с людьми с посттравматическими стрессовыми расстройствами, расстройствами адаптации и др. Проанализированы возможности использования самопомощи, дебрифинга и т. д. в работе с работниками правоохранительных органов, которые выполняли служебные обязанности в нетипичных условиях. Показана действенность разных методов психологии в зависимости от этапа предоставления психологической помощи и сложности симптоматики. Настаивается, что психологическое самообразование, взятие ответственности на себя за своё состояние, овладение навыками правильного поведения и позитивное мышление являются важными в реабилитации правоохранителей, выполнявших служебные задания в нетипичных условиях.
Psychological assistance for law enforcement officers performed their duties in the atypical conditions
Психологическая помощь работникам правоохранительных органов, выполнявшим служебные обязанности в нетипичных условиях
Кудар, К. В. Психологічна допомога працівникам правоохоронних органів, які виконували службові обов’язки в нетипових умовах / К. В. Кудар // Право і безпека. – 2017. – № 2 (65). – С. 12–17.
Кудар К. В. "Психологічна допомога працівникам правоохоронних органів, які виконували службові обов’язки в нетипових умовах." Право і Безпека 2 (2017): 12-17.
Kudar, K.V. (2017), “Psychological assistance for law enforcement officers performed their duties in the atypical conditions” [“Psykholohichna dopomoha pratsivnykam pravookhoronnykh orhaniv, yaki vykonuvaly sluzhbovi oboviazky v netypovykh umovakh”], Pravo i Bezpeka, No. 2, pp. 12–17.
Keywords: Психологія. Рsychology. Психология; Юридична психологія. Legal psychology. Юридическая психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; психологічна допомога; соціально-психологічна дезадаптація; психотерапія; посттравматичні стресові розлади; антитерористична операція; зона АТО; psychological assistance; psychosocial disadaptation; psychotherapy; post-traumatic stress disorder; ATO-zone; психологическая помощь; социально-психологическая дезадаптация; психотерапия; посттравматические стрессовые расстройства; антитеррористическая операция